Glacier Relics of the Last Glacial and Holocene Periods Discovered in the Middle‐low Mountains of Eastern China: Sedimentary Sequences and Environmental Evolution of Mengshan Mountain in Shandong Province since 80 ka. (28th March 2020) - WANG, Zhaobo; WANG, Jiangyue; HE, Lelong; ZHANG, Jian
Abstract : Abstract: The goal of this research study is to describe academic issues which have been debated in the field of Chinese geosciences for a century. In 1922, Jonquei S. Lee (Li Siguang) discovered Quaternary glacial relics at Taihang Mountainin eastern China. In 1947, he published his research findings in the magazine Mount Lushan in Glacial Age . The research results had established three Ice Ages: Poyang (Gonzi), Dagu (Minde), and Lushan (Lisi). However, at that time, no Wurm glacial relics of the last Ice Age had been found in Lushan Mountain. Since then, the research team represented by Shi Yafeng, who is considered to be "the father of glaciers in China", questioned Jonquei S. Lee's research results and concluded that "Professor Jonquei S. Lee's Quaternary glacier research in Lushan Mountain having misread the debris flow". In 2005, the "middle‐low mountains" in eastern China were finally defined as follows: "We clearly and unambiguously believe that there were no glacial activities in the middle‐low mountainous areas of eastern China (east of 102° to 104°E; below 3, 000 and 2, 500 m) during the Quaternary Period". Currently, the long‐standing academic debate appears to have come to a conclusion. As of 2015, the author and others began to investigate and study the Quaternary glacial relics in Mengshan Mountain (1, 156m above sea level), Shandong Province, one of the "middle‐low mountains" of eastern China. The relics have been observed to posses the systematic features of glacial erosion, trough and valley striations, and moraine deposits. The applied dating method shave confirmed that there were not only glacial relics of the last Ice Age (Wurm), but also Holocene glacial relics in the Mengshan Mountain area. Therefore, in order to further establish the corresponding relationship between the glacier, loess, stream sediment series, and MIS in the Mengshan Mountain area, a large number of chronological studies have been carried out regarding the various types of sediments in the area, and 24 dating datahave been obtained using OSL, CRN, and 14 Cmethods. On this basis, the corresponding relationship between the sedimentary sequences and the MIS was established for the first time in eastern China, which in dicates the environmental changes which had occurred in eastern China since 80ka. These discoveries s and chronological study results confirm the existence of the Last Ice Age, as well as Holocene glacial relics at Mengshan Mountain, there by confirming that Quaternary glaciation had occurred in the middle‐low mountain areas of eastern China.